Brand Characteristics, Materialism, and Brand Addiction: Psychological Impacts on Indonesian K-Pop Fans - Jonathan Albert; Margaretha Pink Berlianto (International Journal of Economics Development Research (IJEDR), 2025)
The rising popularity of K-Pop culture has influenced consumer behavior in Indonesia, leading to the phenomenon of brand addiction, an extreme emotional attachment to brands. While prior research has explored the origins of addiction to physical goods, research on brand addiction in the entertainment industry, particularly within Asia’s collectivist context, remain limited. This study examines the influence of brand characteristics (hedonism, self-expressiveness, innovativeness, authenticity) and materialism orientation on brand addiction, along with its psychological effects (brand exclusiveness, trash-talking, compulsive buying behavior, irritability) among K-Pop fans in Indonesia, using Social Identity Theory (SIT). A cross-sectional survey of 192 respondents was conducted from February to March 2025, with data analyzed via PLS-SEM. Results indicate that brand self-expressiveness, brand innovativeness, and materialism significantly and positively affect brand addiction, while brand hedonism and authenticity show no significant impact. Furthermore, brand addiction positively and significantly influences brand exclusiveness, trash talking, compulsive buying behavior, and irritability. Theoretically, these findings reinforce SIT’s relevance and highlight the need for a brand addiction model in entertainment contexts like K-Pop. Practically, K-Pop agencies and local entertainment businesses should prioritize self-expressiveness and materialism through identity narratives and exclusive merchandise, while implementing strategies like purchase limits and transparent communication to mitigate negative effects like trash talking without dampening fandom enthusiasm.